How we work: Reflecting on ten years of inclusive research - Garcia Iriarte, Edurne (My University, 2021)
Inclusive research has gained momentum internationally. However important critiques of this approach query whether inclusive research reinforces perceptions of deficit and contribute to exclusionary practices. This paper presents a reflection on the practices within an inclusive research group over the past decade, with a focus on decision making and support. The authors used thematic analysis to critically review minutes, workshop presentations and research reports. The findings indicate a shift in how the group works together; moving away from being guided by university supporters in the early years towards increased participation in decision making and ownership of the group’s agenda by self-advocates over time although balanced collaboration across all members continues to be challenging. The article explains how the inclusive approach used by the group enabled self-advocates to not only conduct research, but to also critically review their own work. Points of interest: Research done together with people with learning disabilities, inclusive research, has become known worldwide. Some people wonder if teams that say they are inclusive are not really treating people as equal partners. Our group wanted to reply to these key issues as we think about how we work together. To do this, we looked at our meeting notes and agendas, reports, and training presentations over the past ten years. We looked at how we make decisions and the support we get. The group found that self-advocates and supporters now work as full partners. University supporters made decisions before. Now self-advocates decide the research topics, methods, and the report. In this article we explain how we work together and also what we think about the work we do. Even though we are happy with the way we work, we still struggle with how much work we all do.
ACCEPTED
Keywords: Inclusive research; Learning disabilities; Support; Decision making; Training; Inclusive Society; Inclusive research; Ireland